Association between fine particulate matter and coronary heart disease: A miRNA microarray analysis. (15th November 2022) - Guo, Jianhui; Xie, Xiaoxu; Wu, Jieyu; Yang, Le; Ruan, Qishuang; Xu, Xingyan; Wei, Donghong; Wen, Yeying; Wang, Tinggui; Hu, Yuduan; Lin, Yawen; Chen, Mingjun; et al.
Abstract: Several studies have reported an association between residential surrounding particulate matter with an aerodynamic diameter ≤2.5 μm (PM2.5 ) and coronary heart disease (CHD). However, the underlying biological mechanism remains unclear. To fill this research gap, this study enrolled a residentially stable sample of 942 patients with CHD and 1723 controls. PM2.5 concentration was obtained from satellite-based annual global PM2.5 estimates for the period 1998–2019. MicroRNA microarray and pathway analysis of target genes was performed to elucidate the potential biological mechanism by which PM2.5 increases CHD risk. The results showed that individuals exposed to high PM2.5 concentrations had higher risks of CHD than those exposed to low PM2.5 concentrations (odds ratio = 1.22, 95% confidence interval: 1.00, 1.47 per 10 μg/m 3 increase in PM2.5 ). Systolic blood pressure mediated 6.6% of the association between PM2.5 and CHD. PM2.5 and miR-4726-5p had an interaction effect on CHD development. Bioinformatic analysis demonstrated that miR-4726-5p may affect the occurrence of CHD by regulating the function of RhoA. Therefore, individuals in areas with high PM2.5 exposure and relative miR-4726-5p expression have a higher risk of CHD than their counterparts because of the interaction effect of PM2.5 and miR-4726-5p on blood pressure. Graphical abstract: Image 1 Highlights: Individuals exposure to high PM2.5 concentrations had higher risks of coronary heart disease. The PM2.5 -coronary heart disease association was in part mediated by systolic blood pressure. PM2.5 and miR-4726-5p had an interaction effect on blood pressure to affect the occurrence of coronary heart disease.